2018
DOI: 10.1177/0263617418807829
|View full text |Cite
|
Sign up to set email alerts
|

Development of temperature-induced strains in coal–CH4 and coal–CO2 systems

Abstract: Expansion/contraction of coal, induced by the sorption of carbon dioxide and methane in isothermal and non-isothermal conditions, was measured. The investigation is of great importance in the context of validating the potential CO 2 sequestration in unmined coal seams. Changes in temperature in underground coal beds can influence the sorption balance, resulting in strains in coal strata, which could lead to the desorption of gas and leaks to the ground surface. The research shows that the strains induced by CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The respective values of temperature and pressure are given in the figure. The nonmonotonic behavior is caused by a competition between the pressure and temperature effects, which act in opposite directions; 36 see more details in the Supporting Information, Section S2. Pure component adsorption and strain sharply increase with the depth up to 500 m due to the pressure increase by an order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The respective values of temperature and pressure are given in the figure. The nonmonotonic behavior is caused by a competition between the pressure and temperature effects, which act in opposite directions; 36 see more details in the Supporting Information, Section S2. Pure component adsorption and strain sharply increase with the depth up to 500 m due to the pressure increase by an order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…The progress in theoretical modeling is hindered by a lack of systematic experimental studies of adsorbent deformation during multicomponent adsorption. Most papers report the results of either adsorption or strain measurements, but rarely both. The comprehensive experimental data sets presented in this paper represent the unique exception.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the decreasing relationship of adsorption capacity with temperature, Pan et al [7] indicated that the coal samples do not show significant differences in coal methane adsorption capacity at high temperatures (i. e., 50 and 70 °C). Baran et al [8] point out that changes in temperature in underground coalbeds can influence the sorption balance, resulting in strains in coal strata, which could lead to the desorption of gas and leaks to the ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…described by stretching parameter b and rate coefficient k. The idea behind using this model for coal sorption processes can be easily explained. The physical changes that coal undergoes when exposed to solvents are similar to those of glassy polymers, and their structures are often compared, as both materials exhibit viscoelasticity and swelling behaviour[108] Staib et al (2015). [124] used the above model for describing the sorption kinetics for medium-volatility, bituminous coals with a wide range of maceral composition.…”
mentioning
confidence: 99%